Psychiatric comorbidities of adults with early- and late-onset attention-deficit/hyperactivity disorder. (June 2016) - Lin, Yu-Ju; Yang, Li-Kuang; Gau, Susan Shur-Fen
Objective: We evaluated the psychiatric comorbidities in adults who were diagnosed with Diagnostic and Statistical Manual of Mental disorders, 5th edition attention-deficit/hyperactivity disorder as a function of recalled symptom onset before and after the age of 7 years and whether the childhood attention-deficit/hyperactivity disorder symptoms were associated with psychiatric comorbidities. Method: In all, 214 adults who were diagnosed with Diagnostic and Statistical Manual of Mental disorders, 5th edition attention-deficit/hyperactivity disorder and 174 non-attention-deficit/hyperactivity disorder controls (aged 17–40 years) received psychiatric interviews to confirm their previous and current attention-deficit/hyperactivity disorder status and other psychiatric diagnoses. Demographics and risks of lifetime psychiatric disorders were compared among three groups: (1) attention-deficit/hyperactivity disorder, onset <7 years (early-onset); (2) attention-deficit/hyperactivity disorder, onset between 7 and 12 years (late-onset) and (3) non-attention-deficit/hyperactivity disorder controls. We also tested the effects of attention-deficit/hyperactivity disorder symptoms on the risk of later psychiatric comorbidities by Cox regression analyses. Results: Regardless of the age of onset, attention-deficit/hyperactivity disorder was significantly associated with a wide range of psychiatric comorbidities. There were similar comorbid patterns between early- and late-onset attention-deficit/hyperactivity disorder. Regardless of attention-deficit/hyperactivity disorder diagnosis, increased severity of attention-deficit/hyperactivity disorder symptoms was associated with higher risks of oppositional defiant disorder, conduct disorder, dysthymia and sleep disorder but not major depression, which was associated with the attention-deficit/hyperactivity disorder diagnosis. Conclusion: Our findings suggest that elevating the threshold of age of onset to 12 years in Diagnostic and Statistical Manual of Mental disorders, 5th edition would not over-diagnose attention-deficit/hyperactivity disorder in the adult population. Recalled childhood attention-deficit/hyperactivity disorder symptom severity was correlated with conduct disorder, oppositional defiant disorder, dysthymia and sleep disorders.